A comparative study between intramuscular oxytocin and intramuscular methyl ergometrine in the active management of third stage of labour - Hema Swapnika, Devi Reddy; G., Prema Priya; Senthil Priya, S.; Allirathinam, A. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare the efficacy of prophylactic IM oxytocin 10U and IM methyl ergometrine 0.2mg on duration of third stage of labour, amount of blood loss during the third stage of labour and associated side effects. Methods: 50 low risk antenatal women with singleton pregnancy at term gestation in vertex presentation admitted for vaginal delivery, were randomly allocated into 2groups of 25 each and managed actively in the third stage of labour either with 10 U oxytocin IM or with 0.2mg methyl ergometrine IM immediately after the birth of the baby. The main outcome measures were the difference between the 2groups with regard to: duration of third stage of labour, blood loss by volume, difference in haemoglobin and haematocrit, need for blood transfusion, additional uterotonics and side effects of drugs. Results: The mean duration of third stage of labour in the oxytocin group was 6.68±2.17min and in methergine group was 6.4±1.93 min. Mean blood loss was 302±75.6ml and 282.8±58.27ml. Mean fall in Hb was 0.92gm% and 0.812gm%. Mean fall in PCV was 2.36% and 1.88%. 2women in oxytocin group and 1woman in methergine group received additional 0.2mg methergine. 3women in both groups received 1unit of blood transfusion. 8women who received methergine had side effects while only one in the oxytocin group, with a p value 0.004 which is statistically significant. Conclusions: This study has shown that both oxytocin and methylergometrine were equally efficacious. However, oxytocin had significantly better safety profile and lesser contraindications for usage.